2014
DOI: 10.1371/journal.pone.0098266
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Lipodepsipeptides Produced by Pseudomonas spp. Naturally Present in Raw Milk Induce Inhibitory Effects on Microbiological Inhibitor Assays for Antibiotic Residue Screening

Abstract: Two Pseudomonas strains, identified as closely related to Pseudomonas tolaasii, were isolated from milk of a farm with frequent false-positive Delvotest results for screening putative antibiotic residues in raw milk executed as part of the regulatory quality programme. Growth at 5 to 7°C of these isolates in milk resulted in high lipolysis and the production of bacterial inhibitors. The two main bacterial inhibitors have a molecular weight of 1168.7 and 1140.7 Da respectively, are heat-tolerant and inhibit Geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…[12b, [15][16]18] For example, although several strains produce viscosin as the main CLP, in other strains massetolide A is the most abundant with viscosin appearing as a minor product. [12a] Gerard et al [12b] demonstrated that the NRPSs exhibit a certain degree of flexibility in selecting the free amino acids, thus providing an explanation for this variation.…”
Section: Introductionmentioning
confidence: 99%
“…[12b, [15][16]18] For example, although several strains produce viscosin as the main CLP, in other strains massetolide A is the most abundant with viscosin appearing as a minor product. [12a] Gerard et al [12b] demonstrated that the NRPSs exhibit a certain degree of flexibility in selecting the free amino acids, thus providing an explanation for this variation.…”
Section: Introductionmentioning
confidence: 99%
“…As far as we know, only two Pseudomonas strains isolated from dairy product were shown to produce cyclic lipopeptides. However, those two strains, closely related to P. tolaasii , were shown to produce isoforms belonging to another family (viscosin) ( Reybroeck et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The bacterium Pseudomonas “ reactans ” was recently re-classified as P. fluorescens (Ghequire et al, 2013 ). The incidence of CLP producers in milk is not well known, but a recent report demonstrated the implication of CLP production in false positive results when screening for antibiotic residues in milk (Reybroek et al, 2014 ). Considering that tolaasin had an inhibitory effect on Bacillus subtilis and B. megaterium (Rainey et al, 1991 ) and that C1 is also a CLP producer, both representatives of two different types of CLPs producers, C1 and P. tolaasii LMG 2342 T , were selected in this study.…”
Section: Discussionmentioning
confidence: 99%